Qualitative and quantitative study of intermolecular weak interactions for aminosalicylic acid isomers by terahertz spectroscopy. Issue 20 (28th June 2022) - Tang, Yuan; Li, Zhi; Tu, Shan; She, Yulai; Gan, Yongying
Abstract: In the field of chemical science, the development of new drugs, the formation of crystals and molecular clusters, and the optimization of drug safety and efficacy are all closely related to weak molecular interactions. In this paper, the salicylic drugs 4‐aminosalicylic acid (4‐ASA) and 5‐aminosalicylic acid (5‐ASA) are used as the research objects. First, the terahertz (THz) absorption spectra of the two isomers were measured in the range of .4–2.0 THz by terahertz time‐domain spectroscopy (THz‐TDS). Then the unit cells were calculated by using density functional theory (DFT). We found that the characteristic absorption peaks of the experimental spectra were basically consistent with the theoretical calculation. In addition, under the solvent model, the free energy of dissolution and the free energy of the systems were considered and calculated, and the results showed that solvation had a certain influence on the position and intensity of spectral absorption peaks. In order to further explore the origin of the characteristic absorption peaks, the vibrational properties of the unit cell model were analyzed using the potential energy distribution (PED) method. At the same time, the weak interactions of the system were qualitatively and quantitatively analyzed by interaction region indicator (IRI) and energy decomposition analysis based on forcefield (EDA‐FF) methods, respectively. The results show that the absorption peaks of 4‐ASA and 5‐ASA are mainly derived from the vibration mode of dihedral angle torsion. The weak interactions in the 4‐ASA are dominated by dispersion, while they are dominated by electrostatic and dispersion in the 5‐ASA. Therefore, it is an effective way to identify isomers and study intermolecular weak interactions by using THz‐TDS combined with PED, IRI, and EDA‐FF. Abstract : The terahertz spectrum of substance is unique. The theoretical calculation provides a reasonable prediction and verification for the experimental results, and also characterizes the rationality of the model and calculation methods. The results indicate that the characteristic absorption peaks of the experimental spectra are basically consistent with the theoretical calculations. In addition, solvation has a certain influence on the position and intensity of the spectral absorption peaks.